Fibonacci-Like Sequence - Bhatnagar, Shikha; Singh, Bijendra; Sikhwal, Omprakash (International Journal of Advanced Mathematical Sciences, 2013)
The Fibonacci and Lucas sequences are well-known examples of second order recurrence sequences, which belong to particular class of recursive sequences. In this article, Fibonacci-Like sequence is introduced and defined by The Binet’s formula and generating function of Fibonacci-Like sequence are presented with some identities and connection formulae.